Ignition delay times of single kerosene droplets based on formaldehyde LIF detection. (1st March 2016) - Burkert, A.; Paa, W.
Graphical abstract: Highlights: Measurement of ignition delay times of single fuel droplets. Fuels: Jet A-1, GTL kerosene, Exxsol D80. Background corrected LIF images. Cold and hot ignition start by formaldehyde LIF appearance and depletion. Ignition delay times of cold and hot ignition. Abstract: Single droplet ignition experiments were performed with GTL kerosene, Jet A-1, and Exxsol D80 (reduced aromatics) in the temperature range from 550 to 900 K in air at 3 bar. The laser-induced fluorescence (LIF) intensities of liquid GTL kerosene and Exxsol D80 are on a lower level than that of Jet A-1. Formaldehyde LIF and background emission were measured with pulse-to-pulse wavelength switching at closely spaced excitation wavelengths (353.373 and 353.386 nm). Typically, formaldehyde LIF and background emission were observed simultaneously. However, in some droplet ignition sequences background emission was observed first followed by formaldehyde LIF after a time delay. Therefore, in the case of kerosene background subtraction has to be performed carefully to derive correct ignition delay times based on formaldehyde LIF (cool flame). A pulsating combustion was observed in several kerosene droplet ignition experiments. The cool flame ignition was found to appear significantly earlier for the synthetic GTL kerosene compared to Exxsol D80 and conventional Jet A-1 kerosenes. For GTL kerosene we found a cool flame ignition delay time of 624 ms, while corresponding values for Exxsol D80 and Jet A-1 amount to 1467 and 1699 ms, respectively. The differences for the starting time of hot ignition (around 1050 ms) and ignition temperatures (near 700 K) are comparatively small under the conditions of our experiments.